Synthesis and properties of quinazoline-based versatile exciplex-forming compounds - Keruckiene, Rasa; Vekteryte, Simona; Urbonas, Ervinas; Guzauskas, Matas; Skuodis, Eigirdas; Volyniuk, Dmytro; Grazulevicius, Juozas V. (Beilstein Journal of Organic Chemistry, 2020)
Three compounds, bearing a quinazoline unit as the acceptor core and carbazole, dimethyldihydroacridine, or phenothiazine donor moieties, were designed and synthesized in two steps including a facile copper-catalyzed cyclization and a nucleophilic aromatic substitution reaction. The photophysical properties of the compounds, based on theoretical calculations and experimental measurements, as well as the electrochemical and thermal properties, are discussed. The synthesized compounds form glasses with glass-transition temperatures ranging from 116 °C to 123 °C. The ionization potentials estimated by cyclic voltammetry of the derivatives were in the range of 5.22–5.87 eV. The 3,6-di-tert-butylcarbazole-substituted quinazoline-based compound forms a sky-blue emitting exciplex in solid mixture with the acceptor 2,4,6-tris[3-(diphenylphosphinyl)phenyl]-1,3,5-triazine as well as an orange emitting exciplex with the donor 4,4′,4″-tris[3-methylphenyl(phenyl)amino]triphenylamine. A white OLED based on these versatile exciplex systems with a relatively high maximum brightness of 3030 cd/m2 and an external quantum efficiency of 0.5% was fabricated.
Keywords: carbazole; dimethyldihydroacridine; exciplex; phenothiazine; quinazoline